PENERAPAN MODEL PEMBELAJARAN RECIPROCAL TEACHING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA - Eni Tri Budianti; Helma Mustika (Universitas Islam Sumatera Utara, 2017)
This research is motivated by the low understanding of the concept by students of science class XI SMA Negeri 1 Rengat Barat. The purpose of this study is to determine the ability to understand the mathematical concepts of students by class XI IPA SMA Negeri 1 Rengat Barat.This type of research is quasi exsperiment with randomyzed subject posstest only control group design. The analysis technique in this test is t-test. Based on the hypothesis test calculation its shows the significant value of the sample class is smaller than α that is 0.006 0.05. This means that it can be concluded that the ability to understand the concept of mathematics using the reciprocal teaching learning model is better than the ability to understand the concept of mathematics by using conventional learning model.